2011
DOI: 10.1007/s10549-011-1632-x
|View full text |Cite
|
Sign up to set email alerts
|

HER2 discordance between primary breast cancer and its paired metastasis: tumor biology or test artefact? Insights through meta-analysis

Abstract: The proto-oncogene, HER2, has prognostic and predictive relevance in invasive breast cancer (IBC). HER2 testing of primary IBC guides treatment selection and is assumed to reflect HER2 status of associated metastases, although HER2 discordance between IBC and metastasis has been reported. Systematic review and meta-analysis of HER2 status in IBC and its paired loco-regional or distant metastasis were done. Quality appraisal considered whether (within-subject) testing conditions were maintained for paired prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 54 publications
2
69
1
3
Order By: Relevance
“…There are several indications for various types of tumors that in cases where the expression of members of the epidermal growth factor receptor (EGFR) family is high in the primary tumor, it may also be high in the metastases (2)(3)(4). The reason for this may be that the receptor-expressing tumor cells require the growth factor-receptor interactions for growth stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…There are several indications for various types of tumors that in cases where the expression of members of the epidermal growth factor receptor (EGFR) family is high in the primary tumor, it may also be high in the metastases (2)(3)(4). The reason for this may be that the receptor-expressing tumor cells require the growth factor-receptor interactions for growth stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in HER2 expression of primary breast cancer and metastases have been reported. Metaanalysis of 26 studies including 2,520 patients revealed discordance in HER2 expression between the primary tumor and local lymph node metastases in the range of 2.4%-7.2% and discordance with distant metastases in the range of 6.9%-18.6%, with an absolute variation for all studies in the range of 0%-40% (12). A recent symposium publication including 2,845 patients reported absolute variations in the same range (13).…”
mentioning
confidence: 96%
“…Today, assessment of HER2 status is based on tumor biopsy. However, HER2 expression can vary between the primary tumor and metastases in up to 40% of cases (2,5,6) and metastatic HER2 expression can change over time, which could necessitate a change of therapy (7,8). Follow-up using biopsies cannot always be performed due to practical reasons or patient discomfort.…”
mentioning
confidence: 99%